NEW DEVELOPMENTS IN CENTRAL ASIAN MASS MEDIA RESEARCH - FREEDMAN, Eric; SHAFER, Richard (CENTRAL ASIA AND THE CAUCASUS, 2011)
The end of the Cold War represented an apparent victory for NATO, capitalism, free enterprise, and democracy over the Warsaw Pact, Marxism-Leninist communism, and the Russian Soviet empire. In 1991, five newly independent republics of Central Asia (Kazakhstan, Kyrgyzstan, Turkmenistan, Tajikistan, and Uzbekistan) emerged from the wreckage of that watershed event. Each new government proclaimed its commitment to free enterprise economic systems and democratic governance. Western democracies, nongovernmental organizations (NGOs), and human rights groups lauded that commitment to democratic mass media systems as stabilizing, modernizing, and nation-building tools. Unfortunately, significant obstacles remain to functional and effective press systems able to maintain economic, editorial, and political autonomy. Because Russian and Soviet-era press conventions still strongly influence the press in Central Asia, this article begins with a brief overview of the Russian colonial and czarist press system from the 1860s to the Russian Revolution of 1917. It then presents a brief history of press controls under the Soviet Union. Thus, forms of Russian domination of Central Asian journalism persisted for almost 130 years, leaving deeply entrenched czarist-Soviet press methods, controls, and traditions. The study then summarizes significant arenas of contemporary research on Central Asian mass media, including detailed evidence of the complexity, diversity, and depth of barriers to free and effective press systems. It establishes that imposed Soviet-era journalism philosophy and practices remain much of the foundation for current professional ideology. Although there were some positive aspects to the Soviet press system, inherited professional habits, conventions, ideology, and socialist economics still obstruct adoption of aspects of Western models hallmarked by independent journalism and advocacy of a more operative form of social responsibility to audiences. The article then outlines the conflict between external and internal pressures to establish free and democratic press systems where regimes actively resist such efforts. That resistance includes formal and informal policies of censorship and repression that restrain journalists and the mass media they serve.